2003
DOI: 10.1111/j.1545-5300.2003.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

An Outcome Evaluation of the Implementation of the Triple P‐Positive Parenting Program in Hong Kong

Abstract: The present study evaluated the effectiveness of the Positive Parenting Program (Triple P) with a sample of Chinese parents of children with early onset conduct-related problems in Hong Kong. The participants consisted of 91 parents whose children attended maternal and child health centers and child assessment centers for service, and were between three to seven years old. Participants were randomly assigned to the intervention (TP) and a waitlist control group (WL). There was no significant difference in pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
175
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(201 citation statements)
references
References 31 publications
19
175
1
3
Order By: Relevance
“…The results support previous findings on the efficacy of Triple P in various international studies (e.g., Bodenmann, Cina, Ledermann, & Sanders, 2008;Heinrichs et al, 2006;Leung, Sanders, Leung, Mak, & Lau, 2003;Sanders, 1999;Sanders et al, 2007;Sanders & Dadds, 1993). Additionally, de Graaf et al (2008) in a meta analysis showed that Triple P is an effective method for strengthening parenting competencies and for improving children's behavior and well-being yielding within-group effect sizes of d = .55 to 1.46 and between-group effect sizes of d = .50 to 1.27 (for post and follow-up measurements up to one year).…”
Section: Discussionsupporting
confidence: 82%
“…The results support previous findings on the efficacy of Triple P in various international studies (e.g., Bodenmann, Cina, Ledermann, & Sanders, 2008;Heinrichs et al, 2006;Leung, Sanders, Leung, Mak, & Lau, 2003;Sanders, 1999;Sanders et al, 2007;Sanders & Dadds, 1993). Additionally, de Graaf et al (2008) in a meta analysis showed that Triple P is an effective method for strengthening parenting competencies and for improving children's behavior and well-being yielding within-group effect sizes of d = .55 to 1.46 and between-group effect sizes of d = .50 to 1.27 (for post and follow-up measurements up to one year).…”
Section: Discussionsupporting
confidence: 82%
“…These include trials with parents in Hong Kong (Leung, Sanders, Leung, Mak, & Lau, 2003), Japan (Matsumoto, Sofronoff, & Sanders, 2007), Germany , Switzerland (Bodennman, Cina, Ledermann, & Sanders, 2008), Australia (Sanders, Markie-Dadds, Tully, & Bor, 2000), and New Zealand (Venning, Blampied, & France, 2003).…”
Section: Ensure That Culturally Appropriate Programs Are Availablementioning
confidence: 99%
“…On the contrary, ethnic and cultural differences may influence whether parents participate at all in a parenting program, whether they consider a behavior a problem, and whether they consider different parenting and disciplinary methods acceptable. Strategies we have employed to ensure cultural relevance of Triple P include soliciting consumer opinion about the parental strategies advocated; conducting focus groups of elders, service providers, and parent consumers to identify key concerns and issues relevant to program implementation with specific ethnic groups; translating materials; reshooting video materials to ensure that indigenous families are included; using voice-synchronized dubbing of selected video material; and conducting outcome research with different ethnic groups to examine the efficacy of the culturally adapted procedures (e.g., Leung et al, 2003).…”
Section: Ensure That Culturally Appropriate Programs Are Availablementioning
confidence: 99%
“…[1][2][3][4][5] Disruptive behavior problems, such as defiance and anger, put children at high risk for oppositionaldefiant disorder and conduct disorder, and carry a high burden for individuals and society as a whole: they are common, persistent, and costly. 6 Parenting interventions based on (social) learning theory are an effective, and cost effective, strategy to reduce disruptive child behavior across countries and cultures.…”
Section: For Publication In Journal Of the Americmentioning
confidence: 99%